Symptom trajectories into eating disorders: A systematic review of longitudinal, nonclinical studies in children/adolescents - McClelland, Jessica (Eur Psychiatry, 2020)
BACKGROUND. Eating disorders (EDs) are serious mental illnesses that can be life-threatening. Stage of illness models and early intervention strategies could be informed by a better understanding of symptomatology that precedes the onset of an ED. This review aims to explore which symptoms (both ED and other psychiatric disorder-related) exist prior to the onset of an ED and whether there any prospective associations between these symptomatologies. METHODS. A systematic literature review was conducted in MEDLINE, Embase, and PsycINFO for large, longitudinal, prospective studies in nonclinical cohorts of children/adolescents that report symptoms prior to the onset of an ED. A quality assessment of included studies was conducted using the Newcastle-Ottawa Quality Assessment Scale. RESULTS. A total of 22 studies were included, and over half were assessed to be of good quality. Studies identified the presence of a broad range of ED and other psychiatric disorder-related symptoms prior to ED onset. Possible prospective associations were identified, including early eating and feeding difficulties in childhood, to ED-related symptoms (e.g., dieting and body dissatisfaction) and other psychiatric disorder-related symptoms (e.g., anxiety and depression) in childhood/early adolescence, progressing to severe symptomatology (e.g., extreme weight control behaviors and self-harm) in mid-adolescence/emerging adulthood. CONCLUSION. The trajectory of symptoms identified to precede and possibly predict onset of an ED may inform early intervention strategies within the community. Suggestions for further research are provided to establish these findings and the clinical implications of these discussed, in order to inform how best to target prodromal stages of EDs.